Improving The Quality of Hadith Learning Through Academic Supervision By The School Principal And The Implementation of Mind Mapping Media In Grade VIII Of MTs Nahdlatul Muslimin Kudus - Taufiqut Bari (Pubmedia Jurnal Penelitian Tindakan Kelas Indonesia, 2026)
This research aims to improve the quality of Hadith learning through the application of academic supervision by school principals and the use of mind mapping media in Islamic Religious Education learning. This study uses the Classroom Action Research (PTK) approach with the Kurt Lewin model which is carried out in two cycles, including the stages of planning, action, observation, and reflection. The research subjects consisted of Islamic Religious Education teachers and grade VIII students. Data collection techniques include observation, tests, and documentation, while data analysis is carried out descriptively, qualitatively, and quantitatively. The results of the study showed that in cycle II there was a significant increase in teacher performance, student learning activities, and Hadith memorization ability. The teacher's performance reached 86%, the student's learning activities reached 85%, and the completeness of Hadith memorization reached 88% with an average class score of 81. These findings show that continuous academic supervision and the application of mind mapping media are able to improve the quality of the process and learning outcomes of Hadith. Thus, this study concludes that the synergy between academic supervision and visual-based learning strategies is effectively applied as an effort to improve the quality of Hadith learning and professional development of teachers.